Perkembangan Moral Anak Usia Dini Usia 0-6 Tahun dan Stimulasinya - Juli Afnita; Eva Latipah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2021)
Early childhood is also a group of children aged 0-6 years. So children at an early age as the golden age (Golde Age) which only happens once in their life. Early childhood is a period of development which is very important for his life. Because during this period of development, all the potential that the child has, needs encouragement that can develop optimally. At this time one of the attitudes that children must have is to be a good and right human being towards their parents, teachers and in the community. Although the main role of parents is to stimulate their development, teachers in schools are also very necessary in laying the foundation for the moral development of early childhood. Therefore, in the development of moral values, it is closely related to the character of children that must become an habituation in their daily life. With the teacher designing more programmed learning activities and learning media that can lead children to moral values, because it is very influential for early childhood playing in designing interesting games as well as fun to develop morein children's moral development. Early childhood is also a group of children aged 0-6 years. So children at an early age as the golden age (Golde Age) which only happens once in their life. Early childhood is a period of development which is very important for his life. Because during this period of development, all the potential that the child has, needs encouragement that can develop optimally. At this time one of the attitudes that children must have is to be a good and right human being towards their parents, teachers and in the community. Although the main role of parents is to stimulate their development, teachers in schools are also very necessary in laying the foundation for the moral development of early childhood. Therefore, in the development of moral values, it is closely related to the character of children that must become an habituation in their daily life. With the teacher designing more programmed learning activities and learning media that can lead children to moral values, because it is very influential for early childhood playing in designing interesting games as well as fun to develop morein children's moral development.